Discrimination between refractive index and temperature by two cascaded cladding-mode type fiber sensors - Jiang, Meng (2013)
We demonstrated a fiber sensor for simultaneous measurement of refractive index and temperature by cascading one long period grating and one modal interferometer. Cladding mode interference between them was also investigated here.